Conjunctions in Malaysian secondary school English language textbooks - Philip, Alicia; Mukundan, Jayakaran; Hossein, Vahid Nimehchisalem (Australian International Academic Centre, 2012)
The present research aims to investigate the distribution pattern of conjunctions and their ranking in two different corpora, namely the Malaysian school English language Textbook Corpus (Textbook Corpus) and the British National Corpus (BNC). An additional objective of the study was to find out how conjunctions had been presented in the Malaysian school English language textbooks (Forms 1-5). The method applied was qualitative content analysis. The findings indicated that coordinating conjunctions were the most frequent conjunctions that occurred in the five textbooks followed by subordinating and correlative conjunctions. The ranking of the different types of conjunctions in the Textbook Corpus was similar to that of the reference corpus, BNC. The results also indicated that the textbooks failed to present conjunctions effectively. The findings are expected to help textbook developers or language teachers in developing or adapting learning materials.